Highly underexpanded rarefied jet flows - Bykov, N. Y.; Gorbachev, Yu. E.; Fyodorov, S. A. (Frontiers in Mechanical Engineering, 2023)
A highly underexpanded jet outflow into a background in the transition and scattering regimes is studied computationally. The direct simulation Monte Carlo method and Navier-Stokes equations are used. The main parameters' impact on the jet flow is analysed. It is shown that a drastic flow structure transformation occurs in a relatively narrow Reynolds numbers' range, 5 ≤Re L ≤ 30, featuring the jet -surrounding gas interaction. At Re L = 5 a shock wave structure typical for underexpanded jet degenerates completely. The existing empirical expressions application for the estimation of characteristic dimensions of shock wave structure in transition regime leads to a significant inaccuracy. For the considered parameters' range the approaches based on the direct simulation Monte Carlo method and Navier-Stocks equations' solution lead to similar results in the nozzle region, where the flow regime is hydrodynamic. Nevertheless the NS approach employment for the assessment of flow parameters within rarefied shock layers is debatable.